Web-based platform for better support to NTU freshmen with special learning need - Jip, Sheng Tat (Nanyang Technological University, 2020)
The goal of this final-year-project (FYP) is to build a website for Nanyang Technological University’s (NTU) freshmen with special needs. Freshmen with special needs are new to NTU environment and they are likely to be unaware of available supports that are relevant to their special needs. As such, this project aims to address this gap. First, this report would provide an introduction on special-need freshmen within Nanyang Technological University (NTU). Needs of special-need freshmen would be explored through a survey, which was conducted on NTU students on Autism Spectrum. At the end of this section, a project goal would be stated along with justifications of the goal. Second, this report would introduce general layout of the website in mobile and desktop view. Apart from this, this report would introduce and explain the purposes for different groups of pages and web application functions that exist within the website. Third, this report would explain some of the important technologies used in this project, including CSS, JavaScript, PHP and MySQL. In addition, this report would explain how the technologies were used for different parts of the website. For example, this report would explain certain CSS codes used to create mobile view and grid view. Finally, this report would offer improvements to the website based on received feedbacks and personal reflections.